Mass spectrometry of methyl and methyl-d3 derivatives of diuretic agents - Yoon, C.N.; Lee, T.H.; Park, J. (1990)
Methyl and methyl-d3 derivatives of 10 diuretic agents were analyzed by electron impact mass spectrometry. The mass spectra and mass fragmental pathways were investigated with deuterated methyl isotopes. ？ 1990 Oxford University Press.
Keywords: acetazolamide; bendroflumethiazide; bumetanide; chlortalidone; diclofenamide; diuretic agent; doping control; etacrynic acid; furosemide; hydrochlorothiazide; mefruside; triamterene; unclassified drug; article; doping; drug analysis; mass spectrometry; methodology; nonhuman; priority journal; Diuretics; Human; Mass Fragmentography